Carbon stock, fluxes, and partitioning in Pinus taeda plantations are affected by genetic variation and stand density in Southeast Brazil - Campoe, Otávio C. [UNESP]; Cordeiro, Natielle G.; Rojas, Gerardo [UNESP]; Albaugh, Timothy J.; Cook, Rachel L.; Rubilar, Rafael A.; Carter, David R.; Alvares, Clayton A. [UNESP]; Maier, Chris A. (Springer Nature, 2025)
BackgroundTo understand how genetic variation among varieties and stand density affect carbon (C), we assessed C stocks, fluxes, and partitioning in Pinus taeda L. plantations in Southeast Brazil. We measured the annual C balance in two consecutive years (from 7 to 9 years after planting) in four different clonal varieties with distinct crown structures (C1-medium, C2-broad, C3-narrow, and C4-broad) and an OP (open-pollinated) family. From age 7 to 8 years, the C balance was assessed for all five varieties at a stand density of 1894 trees ha− 1. From age 8 to 9 years, the C balance was assessed for three varieties (C2, C3, and OP) at two stand densities (low density (LD): 613 trees ha− 1 and high density (HD): 1894 trees ha− 1).ResultsAt age 7–8, the total C stock (above- and belowground plus the litter layer) among varieties ranged from 168 Mg C ha− 1 (C3) to 186 Mg C m− 2 (C1), with the bole as the largest pool (68%). Aboveground net primary production (ANPP) ranged from 1.9 to 3.1 kg C m− 2 year− 1, and total belowground carbon flux (TBCF) from 2.0 to 2.9 kg C m− 2 year− 1. The partitioning of GPP (Gross Primary Production) to ANPP and TBCF reached a maximum value of 35% and 41%, respectively. At age 8–9 years, the C stock was greater in the HD stands than in the LD stands across all varieties. Overall, C stock reached between 103.5 and 184.6 Mg C ha− 1. ANPP under HD was 1.9 kg C m−² year−¹ compared with 0.62 kg C m−² year−¹ under LD. There were no significant differences in TBCF between the HD and LD stands. The partitioning of GPP to ANPP was lower and to TBCF was higher under LD compared with HD.ConclusionRelationship between crown structure and the C stock, fluxes, and partitioning is not clear and should be used with caution for management prescriptions related to C sequestration. Also, no differences in the bole C stock and sequestration were found across varieties within the same planting density. Finally, the genetic variation among varieties and stand density significantly affected stand productivity, with stand density showing greater effect.